Commemoration labor as emotional labor: the emotional costs of being an Israeli militarized national widow. Issue 8 (3rd August 2021) - Ben-Asher, Smadar; Bokek-Cohen, Ya'arit
Abstract: The feminist literature addresses the various modes of gendered militarizing of women's lives; however, little attention has been paid to the issue of militarization of national widows' emotional lives. This study aims at exploring the experience of being a national widow and examining how national widows' lives are militarized even after the husband's death. By analyzing Jewish Israeli national widows' narratives, we show how these widows are expected to serve the state and the military and engage in what we call active 'commemoration labor', i.e. maintaining the glory of the military and aggrandizing its activities. In so doing, these widows are compelled to invest in emotional labor by being publicly visible and faking emotional expressions. At the same time, their close relatives, community, and also society at large expect them to demonstrate empowerment and resilience and to serve as 'ideal' role models for all the other national widows. It is also argued that private grief and bereavement are expropriated and instrumentalized by the masculine state-in-arms in order to justify the continuation of military activities and operations as well as masculine domination of national conflict management.